Diseño accesorio de mecanizado esférico y piezas semiesféricas para tornos de banco C6236X1000 (2025)
This project develops the design of a device for machining spherical and semi-spherical parts in bench lathes model C6236X1000, with the aim of offering an accessible and precise solution for metalworking workshops. The device integrates a worm-rack system that allows controlling the curvature radii with high precision, ensuring the dimensional quality and surface finish of the machined parts. The methodology used included theoretical calculations, numerical simulations and normative criteria based on the AGMA and Norton design principles. Three alternatives were evaluated using a matrix of weighted factors, selecting the final design for its balance between precision, cost and technical feasibility. The calculations included determining the necessary cutting force, sizing the worm-crown system and evaluating the stresses acting on the worm screw, applying Von Mises theory to ensure the structural safety of the device.